Gene expression analysis of chronically stressed Danio rerio treated with aqueous ethanolic Moringa oleifera leaves extract / Muhammad Faiq Najmi Tajudin - Tajudin, Muhammad Faiq Najmi
Anxiety disorder is a mental health condition that affects millions of people worldwide.Common treatments for anxiety include psychotherapy and medications, such as benzodiazepines and selective serotonin reuptake inhibitors (SSRIs).However, these treatments have adverse effects and may not be suitable for everyone. As a result, there is a growing interest in exploring natural remedies for anxiety, including those derived from plants.Moringa oleifera, a plant known for its medicinal properties, has recently gained attention for its potential anxiolytic effects.This plant has been traditionally used to treat various ailments, including anxiety. Nevertheless, there is still a lack of understanding on the mechanism of action of M. oleifera in anxiolytic effects. The aim of this study was to investigate the anxiolytic effects and mechanism of action of ethanolic extracts of M. oleifera (MOLE) leaves,by observing behavioural changes in Danio rerio (zebrafish) and analyzing differential gene expression. For 14-day chronic behavior study, zebrafish were grouped into different treatment groups, including a non-stressed untreated group, stressed untreated group, a positive control group treated with fluoxetine and MOLE treatments group. MOLE was administered at three different concentrations (500 mg/L, 1000 mg/L, and 2000 mg/L) in the stressed treatment groups. The anxiolytic effects were evaluated using the novel tank test (NTT) and light-dark test (LDT). After the behaviour study, RNA was extracted from the fishes’ brains for gene expression analysis using a custom RT² Profiler PCR array. 33 compounds were profiled after LCMS-QTOF analysis. LC50 values of MOLE, 1231 mg/L,were deemed save to be used for this research. Meanwhile, behavior study results showed that 1000 mg/L MOLE significantly reduced anxiety levels in the stress-induced zebrafish group compared to the other treatment groups. The fish also exhibited significant changes in the expression of crhb, faah2a, mao, and pah genes; which potentially affected by MOLE compounds such as quercetin and kaempferol. This study suggests that MOLE may serve as a potential new supplement for anxiety treatment, given its anxiolytic effect on the zebrafish model. However, the result of this study would need to be replicated in other animal models and human before it is marketed as treatment for anxiolytic effects.